Market Research in Global Healthcare - Mahajan, Harshita (My University, 2022)
Market research is the overall procedure of collecting data or information from any particular market or the target consumers of a specific product. There are various techniques of market research which make it possible to gather information from some of the key opinion leaders who are a part of different companies or hospitals around the world. Two projects were completed within the two months of the internship at Growman Research Group. This company majorly conducts market research in the field of healthcare. Quantitative as well as qualitative research was conducted on various medical techniques, devices and diseases for the completion of these two projects. The name of the two projects are APAC Market Assessment and Endocrinology Study respectively. In the first study, we were required to transcribe data gathered through various interviews. We interviewed various individuals like the procurement manager, the quality assurance manager, the quality control manager who worked in different companies which were involved in the manufacturing of variety of medical devices or industrial materials or life science tools. These companies were located in Asian pacific region like India, Singapore, Malaysia, Taiwan, Korea and many others. In the second study, we were required to punch the data through the links after interviewing various endocrinologists in Saudi Arabia who provided insights about the insulin delivery device used by them. These interviews were mainly telephonic interviews.
Keywords: market; research; primary research; qualitative research